Equity in mathematics education : addressing a changing world - Xenofontos, Constantinos; Andrews, Paul (Cognition, equity, & society., 2019)
"Following in the steps of the socio-political turn of the discipline, Equity in mathematics education: Addressing a changing world emerged as a response of the editor and the chapter authors to the enormous changes that have in the last years occurred at a global level (for example, the ongoing war in Syria, the political [in]actions of powerful nations to fight climate change, the rise of far-right parties in many countries around the world, and so on). In recent years, massive migration waves from the Middle East have caused significant demographic changes to many European countries, Canada and the US, that are reflected in schools and classrooms. These observations have led this book's contributors to reconsider the concept and/or practice of equity, and its related concept, social justice, and the role of mathematics education research in addressing and promoting a fairer world. Contrary to other, perhaps highly specialised books concerned with similar topics, this book aims to provide a smooth, yet deep introduction to those who are new to this research area. Equity in mathematics education: Addressing a changing world contributes to the understanding of equity and its complex relations to mathematics education. It is anticipated that it will support individuals in teaching, educational research, policy making and planning, and teacher education, in becoming more aware of the interplay between school mathematics and socio-political issues that, ultimately, impacts the lives of learners and their communities, teachers as practitioners and as citizens, the wider society, and the world as a whole. Even though each chapter can be read independently of others, an engagement with all chapters in this volume will provide readers with a solid holistic understanding of the research territory of equity and mathematics education"--